2011
DOI: 10.1002/etc.577
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of mercury in female river otters (Lontra canadensis) from Nova Scotia, Canada

Abstract: Mercury (Hg) can reach toxic concentrations in aquatic habitats, sometimes as a consequence of human activity. Mercury can have deleterious effects, particularly in piscivorous mammals in which it bioaccumulates. Furs from trapper-provided female otter (Lontra canadensis) carcasses in Nova Scotia were analyzed for total Hg. Concentrations of total Hg in fur samples averaged 25 µg/g dry weight, ranging from 1.4 to 137 µg/g; 20 µg/g is the fur concentration at which toxic effects are expected. Mercury concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Other studies have found that the majority of Hg in fur/hair is OHg, highlighting the importance of fur as a receptacle of OHg from the body (Wolfe et al 1998;Evans et al 2000). THg concentrations in fur, liver, and kidney in otters collected from central Saskatchewan were comparable with concentrations in otters from unimpacted areas within Canada (Kucera 1983;Evans et al 1998Evans et al , 2000Mierle et al 2000;Klenavic et al 2008;Spencer et al 2011).…”
Section: Discussion Hg Concentrations In Tissuesmentioning
confidence: 73%
See 2 more Smart Citations
“…Other studies have found that the majority of Hg in fur/hair is OHg, highlighting the importance of fur as a receptacle of OHg from the body (Wolfe et al 1998;Evans et al 2000). THg concentrations in fur, liver, and kidney in otters collected from central Saskatchewan were comparable with concentrations in otters from unimpacted areas within Canada (Kucera 1983;Evans et al 1998Evans et al , 2000Mierle et al 2000;Klenavic et al 2008;Spencer et al 2011).…”
Section: Discussion Hg Concentrations In Tissuesmentioning
confidence: 73%
“…Other studies have shown similar trends in muscle (Strom 2008) and brain (Mierle et al 2000) tissue. In addition, THg in fur has been used to a greater extent than kidney Hg concentration when examining locational differences in other studies throughout North America (Mierle et al 2000;Yates et al 2005;Klenavic et al 2008;Spencer et al 2011). Using THg in fur was the preferred method for examining geographic differences and is a noninvasive, inexpensive way to monitor Hg over large geographic areas.…”
Section: Geographic Variation In Hg Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean fur THg concentrations (3.76 and 4.96 μg/g) were lowest for colonies located near the coast (Annapolis Royal and West Chezzetcook), which is consistent with trends observed in local freshwater otter populations, and may be associated with increased salt spray exposure. 31 Little brown bats at the two Cape Breton Island sites (Hunters Mountain and Christmas Island) had similarly low mean fur THg values (5.69 and 6.27 μg/g). Although these roosts are positioned further inland, they are located in close proximity to the Bras d'Or lakes, a large system of interconnected mixed freshwater and saltwater basins.…”
Section: ■ Materials and Methodsmentioning
confidence: 88%
“…Moreover, the spatial distribution of fur THg concentrations in female little brown bats at the provincial scale resembles trends observed in Nova Scotia otters, which showed significantly higher fur THg concentrations in the southwest region of the province (with the exception of coastal sites). 31 Furthermore, Yates et al 4 reported that the site variable accounted for 17% of the variation in fur THg concentrations measured in 1447 bats (10 species) captured at 89 sites in northeastern USA.…”
Section: Environmental Science and Technologymentioning
confidence: 99%